Trazabilidad En La Implementación De La Participación De Plusvalía Desde La Ley 388 /97 En El Municipio De Neiva, En El Periodo 2017 - 2020 (2021)
The present research aims to establish the traceability in the execution of the capital gains tax of law 388 of 1987 identifying what have been the impacts of such collection in the municipality of Neiva of the department of Huila, limiting and focusing during the periods from 2017 to 2020; for the development of the research it was necessary, to know and analyze the historical facts that allowed laying the theoretical foundations that gave rise to the momentum of the same, the reasons why the implementation, the collection was late and the fiscal approach given to this contribution, allowed placing the capital gain as a financing tool that favors the physical development of the territorial entities in the exercise of their urban and fiscal independence enshrined in the constitution. For this reason, it was necessary to have knowledge of concepts ranging from the very definition and classification of taxes, the rate and fundamental contributions, the participation in capital gains and its components, among others.